An EFFECTIVENESS OF LEARNING OUTCOMES OF TOURISM GEOGRAPHY TEXTBOOK FOR STUDENT IN GEOGRAPHY EDUCATION STUDY PROGRAM - Murtini, Sri; Sutedjo, Agus; Zain, Ita Mardiani; Sabitah, Sabrina Azharia (Universitas Negeri Surabaya, 2022)
This study aims to determine the effectiveness of the resulting textbook development subject Tourism Geography. Development textbook using the Borg and Gall model with five steps. The steps are (1) initial study to find problems related to geography teaching materials tourism as a product to be developed. (2) create planning development teaching materials, (3) develop products based on the problems found, ( 4 ) conduct field tests on the products being developed, and ( 5 ) revise to correct weaknesses in the field trial phase. The data were obtained from the teaching material validation team, which included material experts, linguists, and learning design experts. The validation results from the expert team showed the textbooks of tourism geography obtain values 92, 4, or category very suitable for learning. While data from the results study class of 2019 programming students subject tourism geography show effective results with an average value of 84.56 or category A-. Keywords: effectiveness, textbooks, geography tourism, learning.